Moral and Legal Problems Reviewed from: "Law no. 12 of 2022 Concerning Sexual Violence” Regarding Sexual Violence Cases in Indonesian Higher Education - Sascha Kezia Cenniago; Alya Zaida Afandi; Celine Loren; Sabina Abigail; Franciscus Xaverius Wartoyo (Journal of Law, Politic and Humanities, 2025)
This research entitled Moral and Legal Problems Reviewed from: "Law no. 12 of 2022 concerning Sexual Violence” Regarding Sexual Violence Cases in Indonesian Higher Education. Sexual violence is one of the problems that arises in society that has received special attention in recent years. Not only sexual violence against the opposite sex, sexual violence between the same sex often shows a significant increase in the higher education environment, both against the opposite sex and the same sex, which has the potential to damage the generation of people who oppose the implementation of the law in Indonesia. This research aims to analyze legal and social views regarding sexual violence that occurs in Indonesian universities. The author uses qualitative research methods and a juridical-sociological approach aimed at looking at the problem of sexual violence from a human rights perspective and the effectiveness of laws and regulations governing sexual violence. The research results show that legal protection efforts for victims of sexual violence are still lacking in the implementation of the law and there is a lack of understanding regarding victims' rights. This statement underlines several important challenges faced in handling cases of sexual violence, namely allowing an increase in same-sex rates, social stigma and legal uncertainty. Therefore, this research suggests that awareness among the public needs to be increased and laws that guarantee recovery for victims of sexual violence.